Strategi Pengembangan Usaha Dagang Menggunakan Analisis SWOT di Perusahaan Coconut Sejahtera - Muhammad Fahrurahman; Jualiana Kadang; Erwan Sastrawan (Universitas Kristen Indonesia Toraja, 2023)
This study aims to formulate alternative business developing strategies that are implemented at Coconut Sejahtera. Data analysis used is SWOT analysis. The results of this study showed that based on the analysis internal environment using the IFAS matrix, the most influential strength factor is being able to read price changes through the international oil price market and the most influential weakness factor is limited capital. Meanwhile, from the external environment analysis with EFAS matrix, the most influential opportunity factor is the abundance of copra commodities and the most influential threat factor is the arrival of large traders from outside the region.